If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3yi) = 4i Reorder the terms: (3iy + x) = 4i Remove parenthesis around (3iy + x) 3iy + x = 4i Solving 3iy + x = 4i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-4i' to each side of the equation. 3iy + -4i + x = 4i + -4i Reorder the terms: -4i + 3iy + x = 4i + -4i Combine like terms: 4i + -4i = 0 -4i + 3iy + x = 0 Add '-1x' to each side of the equation. -4i + 3iy + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 -4i + 3iy + 0 = 0 + -1x -4i + 3iy = 0 + -1x Remove the zero: -4i + 3iy = -1x Combine like terms: -1x + x = 0 -4i + 3iy + x = 0 The solution to this equation could not be determined.
| 2.2c+4.2c-6=c+7 | | -x-1=-4x-19 | | [(x-3)(x-3)]+[(y+4)(y+4)]=36 | | -x+5=3x-31 | | [(x-3)(x-3)]+[(y+3)(y+3)]=36 | | ax-bx+y=z | | ln(2x+5)=3.3 | | (x-6)x=247 | | 100-50x=(10-2x)(10-2x)(4-x) | | (3x-5)+x=(-x+15)+180 | | 2x^2+14x-44=0 | | 100-50x=(10-2x)2(4-x) | | abc*de=fghjk | | 140x+90y=690550 | | x-2=-2x+13 | | y=10log(8-6t^2+t^3) | | 3(x^2-4x)=x+10 | | 2h^2-11q+9=0 | | f(x)=2bx^4+4ax^2-16+12 | | f(x)=ax^3-2bx^2+3bx-4a | | 6cosx=8sinx | | 38/5÷13/5 | | 2x+5-13=5 | | .35n=100 | | 3y=-1x-6 | | a-60=40 | | (2x+1)+(2x-1)-x=5.29150262213 | | N+.35=100 | | 4x+5=4(x-4) | | 2v^2-v-10=0 | | 3e=13 | | 2k^2+9k-11=0 |